2022
DOI: 10.1101/2022.12.22.521380
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Taxonomic and metabolic diversity of Actinobacteria isolated from faeces of a 28,000-year-old mammoth

Abstract: Ancient microbial communities of permafrost soils and frozen animal remains represent an archive that has barely been explored. This yet unexplored microbial world is a vast resource that can provide us with new evolutionary insights, metabolic pathways and novel chemistry. Here, we reveal that Actinobacteria isolated from a faecal sample from the intestinal tract of a 28,000-year-old Siberian mammoth are phylogenetically and metabolically distinct from currently known modern siblings. Ancient Micromonospora, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Rather our Bison , Mammuthus , and Discrotonyx sedaDNA has strong positive correlations here with Clavibacter , Amycolatopsis , Streptomyces , Micromonospora , Pseudonocardia , Methanobrevibacter , and Microlunatus . These species have been found previously to be associated with either cold/permafrost sediments (Deng et al., 2015; Gilichinsky et al., 2008; Wang, Wang, et al., 2021; Zaitseva et al., 2022) or Pleistocene megafauna (Jorns et al., 2020; van Bergeijk et al., 2022).…”
Section: Discussionmentioning
confidence: 80%
“…Rather our Bison , Mammuthus , and Discrotonyx sedaDNA has strong positive correlations here with Clavibacter , Amycolatopsis , Streptomyces , Micromonospora , Pseudonocardia , Methanobrevibacter , and Microlunatus . These species have been found previously to be associated with either cold/permafrost sediments (Deng et al., 2015; Gilichinsky et al., 2008; Wang, Wang, et al., 2021; Zaitseva et al., 2022) or Pleistocene megafauna (Jorns et al., 2020; van Bergeijk et al., 2022).…”
Section: Discussionmentioning
confidence: 80%
“…While there is limited empirical evidence of microbe diversification as a direct result of megafauna extinction, support for this mechanism comes from the theory of island biogeography (Heaney, 2000). Bergeijk et al (2022) recently showed the high degree of phylogenetic and metabolic dissimilarity between Actinobacteria from the gut of a 28,000year-old mammoth and modern members of this bacterial phylum. The authors highlight that these differences may be due to a low number of reference genomes available in certain Actinobacteria taxa.…”
Section: Discussionmentioning
confidence: 99%